IMPLEMENTASI ALGORITMA FAST FOURIER TRANSFORM PADA MONITOR GETARAN UNTUK ANALISIS KESEHATAN JEMBATAN - Fatah, Ahmad (Jurnal Ilmiah Teknologi Infomasi Terapan, 2021)
Bridges are an important part in a road network system, because of their significant influence if the bridge collapses or does not function properly, the collapse of the bridge will disrupt the smooth transportation of people and goods. So a health monitoring system is needed on a bridge. Where the results of this monitoring will produce natural frequency data, stress and deflection. The x, y, and z axis acceleration data will be processed using the Fast Fourier Transform (FFT) algorithm, then the processed frequency data will produce the bridge’s natural frequency. From the results of the study showed that bridge vibration monitoring can be displayed with X, Y and Z axis acceleration data as well as FFT. With a load of 6 KG, the axes acceleration x = 1.29, Y = 0.73 and Z = 13.39, Basic Fermentation X = 1.82, Y = 1.03 and Z = 18.93. For deflection parameters with an accuracy of 99.66%, with a 6Kg load obtained an average error of 11 mm (millimeters) with an average percentage error of 0.0396%. for heavy Teakann parameters with an accuracy of 99.534%, with a load of 6 kg obtained an average error percentage of 0.1821 kg with the highest percentage of errors of 0.4566%. The conclusion obtained from the results of the study that each sensor to calculate health parameters on the bridge prototype with a span of 65cm from the aspect of vibration is classified as not good condition with a vibration value of 1.82 Hz. From the deflection aspect, the bridge is not good, because it has an average deflection of 1mm or 1.1 cm, with a maximum limit of 0.65 cm.